Ratio fluorescence sensing system based on aggregation-induced emission and application thereof

By constructing a dual-emission fluorescence sensing system based on aggregation-induced luminescence, the combination of TPE-NH2-HMSNs and Pen-Au/CuNCs is used to solve the problem of insufficient sensitivity and selectivity of H2S detection methods, and high selectivity and high sensitivity are achieved. Detection, and real-time, quantitative H2S detection is achieved through the smartphone platform.

CN119322044APending Publication Date: 2025-01-17CHINA PHARM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411436437.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing H2S detection methods have poor sensitivity, large instrument size, complex sample preprocessing, long time consuming and susceptible to interference from other biothiols, and single-emitting fluorescent sensors are susceptible to background interference, with limited selectivity and application range.

Method used

A dual emission fluorescence sensing system based on aggregation-induced luminescence is constructed, and the combination of TPE-NH2-HMSNs and Pen-Au/CuNCs is used to achieve fluorescence color changes through strong interaction between metal atoms and H2S, thereby improving the sensitivity and selectivity of detection. And realizes self-correction function through ratio fluorescence sensing and smartphone platform.

Benefits of technology

High selectivity and high sensitivity detection of H2S is achieved, detection limits are reduced, and real-time and quantitative H2S detection is achieved through portable hydrogel beads and smartphone platforms, suitable for water quality and biological samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119322044A_ABST
    Figure CN119322044A_ABST
Patent Text Reader

Abstract

The invention relates to H2S detection, in particular to an aggregation-induced emission-based ratiometric fluorescence sensing system and application thereof.Penicillamine is used as a ligand to synthesize gold-copper nano-clusters (Pen-Au / CuNCs) and tetraphenylethylene modified hollow mesoporous silica (TPE-NH2-HMSNs) of an amino ligand, and the Pen-Au / CuNCs and the tetraphenylethylene modified hollow mesoporous silica are combined to successfully construct an efficient ratiometric fluorescence sensing platform (Au / CuNCs and HMSNs). The sensor is used for selectively detecting H2S, and two analysis methods of solution sensing and solid portable sensing are established. Compared with other methods for detecting H2S reported before, the method provided by the invention has a lower detection limit (0.147 [mu] M). In addition, a novel portable hydrogel bead fluorescence detection device is developed by utilizing color change, and quantitative visual detection of H2S is realized by combining with a smart phone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to 2 S detection, specifically involving ratiometric fluorescence sensing systems based on aggregation-induced emission and their applications Background Art

[0002] Hydrogen sulfide (H 2 S) is closely related to drinking water safety and life systems. 2 S is a key raw material for intermediate chemicals in the plastics, paper, textile, pesticide and coating industries. If H is discharged without permission or exceeds the pollution limit, 2 Industrial wastewater may affect the quality of natural water, cause ecological damage and groundwater pollution, and even directly harm human health. In order to protect public health and the environment, the American Conference of Governmental Industrial Hygienists has set a maximum residual limit of hydrogen sulfide in wastewater of 1 mg·L -1 (29.3μM). Further studies have shown that endogenous H 2 S is also a gaseous signaling compound and a key biological messenger, and is considered a gasotransmitter along with two other known endogenous gasotransmitters, nitric oxide and carbon monoxide. It can be produced endogenously by enzymatic cysteine ​​metabolism. 2 S has many physiological functions, such as anti-inflammatory, anti-tumor, regulating neurotransmission, inhibiting insulin signal transduction, etc. However, abnormal H 2 Low levels of H2S can lead to various diseases such as Alzheimer's disease, Down syndrome, diabetes, and liver cirrhosis. Therefore, there is an urgent need to establish effective methods to monitor H2S in environmental and biological samples. 2 S level.

[0003] Currently, detection of H 2 Common methods for S analysis include electrochemical method, colorimetry, Raman spectroscopy, high performance liquid chromatography and mass spectrometry. Although these analytical methods have achieved certain results, they also have disadvantages such as poor sensitivity, large instrument size, complex sample pretreatment, and long time consumption, which seriously limit their wide application. 2 The detection of S is often interfered by other biothiols, and there is an urgent need to develop a highly selective analytical method. In contrast, the fluorescence method has attracted much attention due to its simple operation, high selectivity, high sensitivity and fast response speed. However, fluorescence sensors based on single emission are easily interfered by background and have a narrow range of applications. Therefore, in view of the defects of the single emission fluorescence sensing system, a new fluorescence signal can be introduced to construct a ratio fluorescence sensing system to further improve the sensitivity and selectivity of the detection, and it has a self-correction function to eliminate background interference. Summary of the invention

[0004] Purpose of the Invention

[0005] The present invention constructs a dual-emission fluorescence sensing system to improve the sensitivity and selectivity of detection, and has a self-correction function to eliminate background interference.

[0006] Technical Solution

[0007] The ratiometric fluorescence sensing system based on aggregation-induced emission is characterized in that it is prepared according to the following steps:

[0008] (1) TPE-NH 2 Preparation of -HMSNs

[0009] TPE-NH 2 The mixture was mixed with CTAB and dissolved in ethanol solution, ammonia water was added and stirred, and TEOS was added dropwise to the solution to obtain the initial mesoporous silica TPE-NH with mesoporous template CTAB. 2 -MSNs; add initial TPE-NH 2 -MSNs and heated at 90-100 °C to synthesize the hollow structure, remove the mesoporous template CTAB, and expand the pore size to obtain TPE-NH 2 -HMSNs;

[0010] (2) Preparation of Pen-Au / CuNCs

[0011] Dissolve Pen in water and add HAuCl 4 , then add Cu(NO 3 ) 2 , stirred to obtain a white suspension, stirred in the dark at room temperature, centrifuged and washed, and then dried to obtain dry Pen-Au / CuNCs powder.

[0012] (3) Preparation of Au / CuNCs@HMSNs

[0013] Pen-Au / CuNCs and TPE-NH 2 -HMSNs were mixed, and then water was added, shaken vigorously, and finally ultrasonicated, centrifuged, and dried to obtain Au / CuNCs@HMSNs powder.

[0014] The aggregation-induced emission ratio fluorescence sensing system is characterized by being prepared according to the following steps:

[0015] (1) TPE-NH 2 Preparation of -HMSNs

[0016] 0.001~0.06g TPE-NH 2and 0.2-1.2 g CTAB are dissolved in 100-500 mL ultrapure water and 80-280 mL ethanol; the mixture is ultrasonically treated for 20-30 min until CTAB is completely dissolved; then, 2-18 mL ammonia water is added to the mixture and stirred for 1-2 h; finally, 2-18 mL TEOS is added dropwise to the solution and reacted at 30-40 ° C for 6-7 h; the obtained mixture is filtered, separated, washed, and dried to obtain an initial mesoporous silica TPE-NH with a mesoporous template CTAB. 2 -MSNs; Next, add 0.1-2.5 g of initial TPE-NH 2 -MSNs, and heated at 90-100°C for 12-36h to synthesize a hollow structure, remove the mesoporous template CTAB, and expand the pore size; after the reaction, centrifuge at 10000rpm for 10-15min to obtain a crude product TPE-NH 2 -HMSNs, the crude product was purified by washing with ethanol and water three times; the purified TPE-NH 2 -HMSNs were freeze-dried for more than 12 h to obtain dry TPE-NH 2 -HMSNs powder;

[0017] (2) Preparation of Pen-Au / CuNCs

[0018] Under magnetic stirring in the dark at room temperature, 60-260 mg of Pen was completely dissolved in 10-100 mL of ultrapure water; then 2-50 mM HAuCl was added. 4 , then add 0.01~0.9M Cu(NO 3 ) 2 After stirring for 5 to 10 minutes, a white suspension was obtained, indicating the formation of Pen-Au / CuNCs; the solution was stirred at room temperature in the dark for 2 to 4 hours; thereafter, in order to remove excess ligands, the obtained Pen-Au / CuNCs solution was centrifuged and washed, and the collected precipitate was dried to obtain dry Pen-Au / CuNCs powder;

[0019] (3) Preparation of Au / CuNCs@HMSNs

[0020] 0.01-0.1 g Pen-Au / CuNCs and 0.005-0.035 g TPE-NH 2-HMSNs were mixed, and then 10-100 mL of ultrapure water was added, and the mixture was shaken vigorously for 2-5 min, and finally ultrasonically treated for 20-30 min to obtain an Au / CuNCs@HMSNs solution and stored at 4°C; the Au / CuNCs@HMSNs solution was centrifuged and washed, and the collected precipitate was dried to obtain Au / CuNCs@HMSNs powder.

[0021] More specifically:

[0022] (1) TPE-NH 2 Preparation of -HMSNs

[0023] 0.006 g TPE-NH 2 and 0.9 g CTAB were dissolved in 300 mL ultrapure water and 180 mL ethanol. The mixture was ultrasonically treated for 20 to 30 min until CTAB was completely dissolved. Then, 8 mL of ammonia water was added to the above mixture and stirred for 1 h. Finally, 6 mL of TEOS was added dropwise to the solution and reacted at 30 to 40 °C for 6 to 7 h. The obtained mixture was filtered, separated, washed, and dried to obtain the initial mesoporous silica (TPE-NH 2 -MSNs). Next, 0.5 g of initial TPE-NH 2 -MSNs, and heated at 90-100°C for 24h to synthesize the hollow structure, remove the mesoporous template CTAB, and expand the pore size. After the reaction, centrifuge at 10000rpm for 10-15min to obtain the crude product TPE-NH 2 -HMSNs, and the crude product was purified by washing with ethanol and water three times. 2 -HMSNs were freeze-dried for more than 12 h to obtain dry TPE-NH 2 -HMSNs powder.

[0024] (2) Preparation of Pen-Au / CuNCs

[0025] 160 mg of Pen was completely dissolved in 40 mL of ultrapure water under magnetic stirring in the dark at room temperature. Then 10 mM HAuCl was added 4 (2 mL), and then 0.1 M Cu(NO 3 ) 2 (0.10 mL), stirred for 5-10 min, and a white suspension was obtained, indicating the formation of Pen-Au / CuNCs. The solution was stirred at room temperature in the dark for 2-4 h. Afterwards, in order to remove the excess ligand, the obtained Pen-Au / CuNCs solution was centrifuged and washed, and the collected precipitate was dried to obtain dry Pen-Au / CuNCs powder.

[0026] (3) Preparation of Au / CuNCs@HMSNs

[0027] Au / CuNCs@HMSNs were synthesized as follows. 0.02 g Pen-Au / CuNCs and 0.015 g TPE-NH 2 -HMSNs were physically mixed, and then 25 mL of ultrapure water was added, shaken vigorously for 2 to 5 min, and finally ultrasonicated for 20 to 30 min to obtain the Au / CuNCs@HMSNs solution and stored at 4 ° C. To prepare the hydrogel, the Au / CuNCs@HMSNs solution was centrifuged and washed, and the collected precipitate was dried to obtain the Au / CuNCs@HMSNs powder.

[0028] Ratiometric fluorescence sensing system based on aggregation-induced emission for H in biological and environmental samples 2 Rapid detection of S.

[0029] Beneficial Effects

[0030] Fluorescent probes have been widely used in many fields, such as biological detection, drug delivery, and food analysis. However, most traditional organic fluorescent materials have aggregation-induced quenching (ACQ) properties. These molecules emit bright light in dilute solutions, but in concentrated solutions or solids, the photoluminescence decreases due to the quenching effect caused by aggregation. Therefore, ACQ fluorescent materials are not suitable for high-concentration analysis, but low probe concentrations will lead to reduced sensitivity, which limits its application in many aspects, including medical applications or electronic devices. At the same time, many organic dyes will naturally aggregate in aqueous media or films, so they are not suitable for concentrations applied to biological systems and result in low signal-to-noise ratios, photobleaching, and poor phototherapy effects. Although many strategies have been used to limit the ACQ effect, the results are not good.

[0031] In 2001, Tang Benzhong et al. first proposed a new concept - aggregation-induced emission (AIE). AIE materials (aggregation-induced emission luminogen, AIEgens) have unique properties opposite to traditional ACQ molecules. Fig.13. AIEgens show weak or negligible emission in dilute solutions, but strong emission in aggregates or solids. Most AIEgens have the common feature of a propeller-like structure: a peripheral aromatic ring that can rotate freely. In its dispersed state, the free intramolecular motion of the peripheral aromatic ring consumes excitation energy and suppresses emission; in the aggregated state, the free rotation of the peripheral aromatic ring is suppressed by neighboring molecules, the attenuation of non-radiative energy is hindered, and strong emission can be observed. It is precisely because of the non-planar molecular structure of AIEgens that the close π-π stacking effect between molecules in the aggregated state is greatly avoided, preventing aggregation-induced quenching.

[0032] Metal nanoclusters are unique AIEgens with a size of less than 10 nm and are characterized by simple preparation, low toxicity, and good photostability. Tetraphenylethylene (TPE) is another AIEgens that was discovered earlier and is the most widely used. It is favored by researchers for its high quantum efficiency and easy-to-control molecular structure. Therefore, we creatively use TPE and metal nanoclusters to construct a ratiometric fluorescence sensing system. However, the non-water solubility of TPE limits its application in daily life, and it is difficult to composite with gold-copper nanoclusters. To solve the above problems, we creatively introduce hollow mesoporous silica. Hollow mesoporous silica (HMSNs) has uniform nanopores and high biocompatibility. The diameter of the nanopores is the same as that of ultrasmall metal nanoclusters, and it has the characteristics of high specific surface area. At the same time, HMSNs is an optically transparent material with a large band gap, making it an ideal framework for fluorescent probes. In addition, it has good hydrophilicity and is easy to achieve functional group modification on the surface of HMSNs. Modifying AIEgens on HMSNs can greatly improve the water solubility of AIEgens and modify them to different electronegativity. Using HMSNs as a framework to combine two AIEgens together (directly modified on the framework or combined with the framework based on electrostatic adsorption) can effectively improve the fluorescence properties, laying a good foundation for the efficient sensing of target analytes.

[0033]

[0034] like Figure 1 As shown, the present invention utilizes blue fluorescent 1-(4-aminophenyl)-1,2,2-triphenylethylene (TPE-NH 2 ) modified silica (TPE-NH 2 A dual-emission fluorescence sensing system (Au / CuNCs@HMSNs) was constructed by combining Au / CuNCs@HMSNs with red fluorescent Pen-modified gold-copper nanoclusters (Pen-Au / CuNCs). Two detection methods for H 2 The present invention selects TPE-NH 2-HMSNs is the reference fluorescence in the ratiometric fluorescence sensing system, and the blue fluorescence emission remains unchanged. AuCu nanoclusters exhibit AIE effect due to ligand-to-metal charge transfer (LMCT). 2 S, through metal atoms and H 2 The strong interaction of S quenches the red fluorescence emission and is therefore selected as the identification fluorescence. 2 As the concentration of S increases, the fluorescence changes from red to blue. The change in the intensity ratio of the two peaks can be used to detect H in lake water and serum samples. 2 Determination of S. The present invention uses a variety of characterization methods such as Fourier transform infrared spectroscopy, ultraviolet-visible absorption spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and X-ray diffraction to confirm whether Au / CuNCs@HMSNs are successfully prepared and the detection principle. In addition, the probe is loaded into the hydrogel to prepare portable hydrogel beads, and integrated with the smartphone platform. The RGB value is read with the help of the color recognition software on the smartphone to achieve real-time on-site analysis. The dual-mode analysis of ratio fluorescence sensing and smartphone platform sensing can meet the analysis needs of different situations, and has the characteristics of high selectivity, high sensitivity, simplicity and economy, safety and non-toxicity, etc., and is expected to play a vital role in the field of water quality assessment and health testing.

[0035] Specifically:

[0036] The present invention uses penicillamine as a ligand to synthesize gold-copper nanoclusters (Pen-Au / CuNCs), tetraphenylethylene modified hollow mesoporous silica (TPE-NH 2 -HMSNs), and the two were combined to successfully construct an efficient ratiometric fluorescence sensing platform (Au / CuNCs@HMSNs) for the selective detection of H 2 S, and established two analytical methods: solution sensing and solid portable sensing. 2 Modification on hollow mesoporous silica greatly improves its water solubility, is safe and non-toxic, and expands the contact area with the analyte, improving the detection effect. At the same time, as a reference fluorescence in the ratio fluorescence sensing system, the blue fluorescence emission remains unchanged. Gold-copper nanoclusters act as recognition fluorescence, and due to the charge transfer from ligand to metal, they exhibit AIE effect, producing strong red fluorescence. When the complex is exposed to H 2 When in S, the copper and H 2 The high coordination effect between S produces Cu-S bonds, leading to non-radiative electron / hole recombination and annihilation in the effective electron transfer process, thereby quenching the red fluorescence emission and achieving the transition of the fluorescence color from red to blue. The formula for fluorescence intensity in solution is F 0 -F in the range of 0.5~40μM increases with the increase of H2 The increase in S concentration is consistent with other previously reported H 2 Compared with the method of S, it has a lower detection limit (0.147μM). In addition, a new portable hydrogel bead fluorescence detection device was developed using color change and combined with a smartphone to realize H 2 Quantitative visual detection of S. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 , Synthesis steps of Au / CuNCs@HMSNs dual-emission sensing system and its detection of H 2 S and schematic diagram of the integration of a smartphone and a solid-state sensing portable device;

[0038] Figure 2 、(a) Preparation conditions of Pen-Au / CuNCs: optimization of copper-gold ratio, (b) Preparation conditions of Au / CuNCs@HMSNs: Pen-Au / CuNCs and TPE-NH 2 -Optimization of the ratio of HMSNs;

[0039] Figure 3 (a) TPE-NH 2 , Pen, Pen-Au / CuNCs, TPE-NH 2 -Infrared absorption spectra of HMSNs and Au / CuNCs@HMSNs, (b) Infrared absorption spectra of Pen-Au / CuNC, TPE-NH 2 -HMSNs, Au / CuNCs@HMSNs and Au / CuNCs@HMSNs with H 2 Fluorescence emission spectrum of S mixture;

[0040] Figure 4 、(a) XRD spectrum of Pen-Au / CuNCs, (b) XPS spectrum of Au / CuNCs@HMSNs, (c) XPS spectrum of Cu 2P, (d) XPS spectrum of Au 4f

[0041] Figure 5 、(a) TEM morphology of Pen-Au / CuNCs at 100nm (diameter distribution of Pen-Au / CuNC), (b) TPE-NH 2 -HMSNs TEM morphology at 500nm (TPE-NH 2 -HMSNs diameter distribution), (c) TEM morphology of Au / CuNCs@HMSNs at 500nm (Au / CuNCs@HMSNs diameter distribution), (d) Pen-Au / CuNCs, TPE-NH 2-Zeta potential of HMSNs and Au / CuNCs@HMSNs;

[0042] Figure 6 , (a) pH stability, (b) temperature stability and (c) time stability of Au / CuNCs@HMSNs;

[0043] Figure 7 、(a)H 2 UV absorption spectrum of S and excitation / emission spectrum of Pen-Au / CuNCs; (b) adding H 2 UV absorption spectra of Pen-Au / CuNCs before and after S addition; (c) after adding H 2 Fluorescence lifetime of Pen-Au / CuNCs before and after S; (d) after adding H 2 XPS spectrum of Cu2P after S;

[0044] Figure 8 、 Effects of different (a) pH, (b) temperature, and (c) incubation time on H 2 The influence of S fluorescence detection system;

[0045] Fig. 9 、(a)H 2 Fluorescence spectra of Au / CuNCs@HMSNs nanocomposites when the S concentration ranges from 0 μM to 100 μM. (b) F0 / F and the relationship between the concentration of H 2 Linear relationship diagram of S (0.5~40μM), (c) with H 2 CIE chromaticity diagram of the color coordinates of Au / CuNCs@HMSNs nanocomposites (x, y) with S changes, (d) the color changes of Au / CuNCs@HMSNs in solution with the change of analyte concentration under 365nm UV light and natural light, from left to right are 0, 0.5, 1, 5, 10, 20, 40 and 100 μM;

[0046] Fig.10 , the impact of different interfering substances on the HS detection system;

[0047] Fig.11 (a) Preparation and detection of solid sensors 2 Schematic diagram of S, (b) the color change of the solid sensor system with the change of the concentration of the analyte under 365nm UV light and natural light, and the (G+B) / G value and the H at different concentrations analyzed by Image J software 2 The linear relationship between S, from left to right, is 0, 0.5, 1, 5, 10, 20, 50, 100, and 200 μM;

[0048] Fig.12 , other interferents and H2 (G+B) / R value of hydrogel beads in the presence of S (Inset: H-containing beads under 365 nm UV light) 2 Comparison of hydrogel beads with other interferents, from left to right: Blank, Glu, Gly, Arg, His, Cys, Gsh, Hcy, Na2S2O3, Na2SO4, KBr, MgCl2, CuSO4, HgCl2, H 2 S, Mix);

[0049] Fig.13 , schematic diagram of ACQ and AIE. DETAILED DESCRIPTION

[0050] Reagents

[0051] Copper nitrate (CuNO 3 ), copper sulfate (CuSO 4 ), glucose (Glu), potassium chloride (KCl), potassium bromide (KBr), sodium chloride (NaCl), magnesium chloride (MgCl 2 ), mercuric chloride (HgCl 2 ), sodium thiosulfate (Na 2 S 2 O 3 ), sodium sulfate (Na 2 SO 4 ) Captopril was purchased from Sinopharm Chemical Reagent Co., Ltd., tetrachloroauric acid (AuCl 4 )、Penicillamine (Pen), Sodium sulfide (Na 2 S) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. Glutathione (Gsh), arginine (Arg), histidine (His), glycine (Gly), cysteine ​​(Cys), homocysteine ​​(Hcy), 1-(4-aminophenyl)-1,2,2-triphenylethylene (TPE-NH 2 ), sodium alginate (SA) were purchased from Shanghai Aladdin Biochemical Co., Ltd., and sodium hydroxide (NaOH) was purchased from Xilong Science Co., Ltd. Hexadecyltrimethylammonium bromide (CTAB), tetraethyl orthosilicate (TEOS), hydrochloric acid (HCl), nitric acid (HNO 3 ), acetic acid, boric acid and phosphoric acid were purchased from Nanjing Chemical Reagent Co., Ltd. All chemical reagents were analytical grade and were not further purified. The ultrapure water used was obtained from a laboratory ultrapure water machine (Milli-Q 18.25 MΩ*cm system).

[0052] Example 1

[0053] 1. Preparation of Au / CuNCs@HMSNs composites

[0054] (1) TPE-NH 2 Preparation of -HMSNs

[0055] 0.006 g TPE-NH 2 and 0.9 g CTAB were dissolved in 300 mL ultrapure water and 180 mL ethanol. The mixture was ultrasonically treated for 20 to 30 min until CTAB was completely dissolved. Then, 8 mL of ammonia water was added to the above mixture and stirred for 1 h. Finally, 6 mL of TEOS was added dropwise to the solution and reacted at 30 to 40 °C for 6 to 7 h. The obtained mixture was filtered, separated, washed, and dried to obtain the initial mesoporous silica (TPE-NH 2 -MSNs). Next, 0.5 g of initial TPE-NH 2 -MSNs, and heated at 90-100°C for 24h to synthesize the hollow structure, remove the mesoporous template CTAB, and expand the pore size. After the reaction, centrifuge at 10000rpm for 10-15min to obtain the crude product TPE-NH 2 -HMSNs, and the crude product was purified by washing with ethanol and water three times. 2 -HMSNs were freeze-dried for more than 12 h to obtain dry TPE-NH 2 -HMSNs powder.

[0056] (2) Preparation of Pen-Au / CuNCs

[0057] 160 mg of Pen was completely dissolved in 40 mL of ultrapure water under magnetic stirring in the dark at room temperature. Then 10 mM HAuCl was added 4 (2 mL), and then 0.1 M Cu(NO 3 ) 2 (0.10 mL), stirred for 5-10 min, and a white suspension was obtained, indicating the formation of Pen-Au / CuNCs. The solution was stirred at room temperature in the dark for 2-4 h. Afterwards, in order to remove the excess ligand, the obtained Pen-Au / CuNCs solution was centrifuged and washed, and the collected precipitate was dried to obtain dry Pen-Au / CuNCs powder.

[0058] (3) Preparation of Au / CuNCs@HMSNs

[0059] Au / CuNCs@HMSNs were synthesized as follows. 0.02 g Pen-Au / CuNCs and 0.015 g TPE-NH 2-HMSNs were physically mixed, and then 25 mL of ultrapure water was added, shaken vigorously for 2 to 5 min, and finally ultrasonicated for 20 to 30 min to obtain the Au / CuNCs@HMSNs solution and stored at 4 ° C. To prepare the hydrogel, the Au / CuNCs@HMSNs solution was centrifuged and washed, and the collected precipitate was dried to obtain the Au / CuNCs@HMSNs powder.

[0060] 2. Stability investigation of Au / CuNCs@HMSNs

[0061] In order to investigate the stability of the fluorescence intensity of the prepared Au / CuNCs@HMSNs under different conditions, the fluorescence intensity ratio I was investigated under different pH, temperature and time conditions. 610 / I 470 The changes of the fluorescence intensity ratio under different conditions were compared to determine its stability range for subsequent detection experiments. First, the pH stability was investigated. 1mL Au / CuNCs@HMSNs was mixed with 1mL PB buffer with pH of 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, and 9.0 at room temperature for 30 minutes, and the fluorescence intensity ratios under different pH conditions were compared. Subsequently, a certain temperature range was set, and Au / CuNCs@HMSNs were placed in a series of temperatures of 5, 15, 25, 30, 45, and 55°C for 30 minutes to compare the fluorescence intensity ratios at different temperatures. Finally, in order to investigate the stability of the composite material over time, the newly prepared Au / CuNCs@HMSNs were placed in a 4°C refrigerator for 1, 3, 7, 15, and 30 days, and their fluorescence intensity was scanned to determine their fluorescence stability.

[0062] 3. Establishment of dual-emission fluorescence system based on Au / CuNCs@HMSNs

[0063] Take 1 mL of Au / CuNCs@HMSNs solution, 1 mL of PB buffer, and 1 mL of 25 μM H 2 S(H in solution 2 S with Na 2 S substitute) in a 5 mL centrifuge tube, react in a 25 ° C water bath for 10 min, scan the emission spectrum in the range of 420-650 nm at an excitation wavelength of 355 nm, and record the fluorescence intensity at 470 nm and 610 nm, i.e., I 470 and I 610 The blank group used ultrapure water instead of H 2 S, calculate the fluorescence intensity ratio of the two peaks I 610 / I 470 , where the blank group ratio is denoted as F 0 , the experimental group is denoted as F, according to F 0-F value, optimize the detection conditions, and select the best conditions for H 2 Determination of S.

[0064] 4. Linearity and range

[0065] Prepare a series of H in the range of 0.5 to 100 μM. 2 S solution, take 1mL of H 2 S solution, 1 mL of pH 3.0 PB buffer, and 1 mL of Au / CuNCs@HMSNs solution were mixed evenly. The blank group was treated with ultrapure water instead of H 2 S, heated in a 25°C water bath for 10 min, scanned and recorded the fluorescence intensity at 470 nm and 610 nm, and calculated the fluorescence intensity ratio of the two peaks I 610 / I 470 , where the blank group ratio is denoted as F 0 , the experimental group is denoted as F, and F is used 0 -F value and H 2 The relationship between the S concentration and the measured value is realized.

[0066] 5. Determination of hydrogen sulfide in plasma samples and lake water

[0067] In order to evaluate the feasibility and practicality of this method, healthy human plasma was first used as the actual sample, and protein precipitation was performed at a ratio of plasma: methanol = 1:3. After centrifugation, the supernatant was diluted by 20 as actual sample No. 1. Secondly, lake water was collected from the school, and the collected water samples were centrifuged at 10,000 rpm for 10 minutes and then filtered with a 0.22 μm filter membrane as actual sample No. 2.

[0068] H 2 Add S reference substance to two actual samples and scan the emission spectrum under the same conditions as 3.3.4, and record F 0 / F value, calculate H in plasma samples and drinking water 2 S recovery rate.

[0069] 6. Construction and application of visual sensing equipment

[0070] In order to expand the H 2 The application of the new dual-emission system constructed by S and Au / CuNCs@HMSNs was to prepare a simple solid sensing device using sodium alginate hydrogel. First, 25 mg Au / CuNCs@HMSNs powder was dispersed into 10 mL 2% sodium alginate (SA) solution, and then the above solution was slowly and evenly dropped into 2% CaCl 2 In-solution built-in fluorescent hydrogel beads with a diameter of 1.5 mm were successfully synthesized via a mild green route.

[0071] Prepare 0.5, 1, 5, 10, 20, 50, 100, 200 μM HO 2 S sample solution. 2 During the S process, 200 μL of pH 3.0 PB buffer and 200 μL of different concentrations of H 2 The S sample solution was mixed in a 3 mL EP tube, and the prepared hydrogel beads were added to the tube and reacted for 10 min in the dark at 25 ° C. Then, under the irradiation of a portable UV lamp with a wavelength of 365 nm, a smartphone was used to take photos to record the color change of the hydrogel beads, and the RGB value of the photo color was read using Image J software.

[0072] result

[0073] 1. Optimization of preparation conditions of Au / CuNCs@HMSNs

[0074] In the process of preparing Pen@Au-CuNCs, penicillamine was used as the initial ligand and reducing agent, copper nitrate as the copper source, and tetrachloroauric acid as the gold source for synthesis. Under the reduction of the ligand, the gold and copper atoms gradually accumulated to form nanoclusters. At the same time, penicillamine has a thiol structure, which can form Cu-S bonds and Au-S bonds with Cu and Au, playing a stabilizing and protective role on the nanoclusters and promoting the generation of Pen-Au / CuNCs.

[0075] Since the fluorescence intensity of gold nanoclusters is greatly affected by the ratio of synthetic raw materials, the copper-gold ratio needs to be optimized to prepare Pen-Au / CuNCs with higher fluorescence intensity. 0.1611 g Pen was completely dissolved in 37.90 mL ultrapure water, and 4.00, 2.00, 1.00, 0.50, and 0.25 mL HAuCl were added respectively. 4 (10 mM). Then 0.10 mL of Cu(NO 3 ) 2 (0.1 mM) and stirred at room temperature for 2 hours to synthesize Pen-Au / CuNCs with copper-gold ratios of 4:1, 2:1, 1:1, 1:2, and 1:4. Scanning its fluorescence intensity, the results are as follows Figure 2 (a) shows that the fluorescence intensity of Pen-Au / CuNCs is optimal when the copper-gold ratio is 2:1. Therefore, the copper-gold ratio of 2:1 was selected in the subsequent experimental synthesis.

[0076] In the process of preparing Au / CuNCs@HMSNs, the intensity of ratio fluorescence was affected by the interaction between Pen-Au / CuNCs and TPE-NH 2 -HMSNs ratio has a great influence. Therefore, it is necessary to optimize the ratio of the two. Pen-Au / CuNCs and TPE-NH 2-HMSNs composite materials with a ratio of 2:1, 4:3, 1:1, 3:4, and 1:2 were scanned for fluorescence intensity. The results are as follows Figure 2 (b) shows that the fluorescence ratio is optimal when the ratio is 4:3. When the ratio is too small, the peak at 470nm is too strong, and when the ratio is too large, the peak at 610 is too strong. Therefore, Pen-Au / CuNCs and TPE-NH 2 -HMSNs ratio is 4:3.

[0077] 2. Characterization of Au / CuNCs@HMSNs

[0078] In order to prove the successful preparation of Au / CuNCs@HMSNs, transmission electron microscopy (TEM), fluorescence emission spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), dynamic light scattering (DLS), Zeta potential and infrared absorption spectroscopy (FT-IR) were used to characterize its optical properties and morphology composition to prove the successful synthesis.

[0079] (1) Infrared absorption spectroscopy characterization (FT-IR)

[0080] like Figure 3 As shown in (a), Pen is at 2609cm -1 The -SH stretching vibration at 1610 cm-1 disappeared from the surface of Pen-Au / CuNCs, confirming the formation of covalent bonds between Pen and bimetallic Au / CuNCs (Au / Cu-SR). -1 The C=O stretching vibration at 1470 nm confirmed that the ligand Pen was successfully closed, once again proving the successful synthesis of Pen-Au / CuNCs.

[0081] TPE-NH 2 -1100cm in the FT-IR spectrum of HMSNs -1 1230cm -1 The peak at corresponds to the SiO absorption peak, which is mainly the vibration between silicon atoms and oxygen atoms in the silica structure, preliminarily proving the synthesis of mesoporous silica. 2 At 3500cm -1 The -NH stretching vibration at TPE-NH 2 -HMSNs show that it is speculated that it is because of TPE-NH 2 In TPE-NH 2 The content of -HMSNs was too low, accounting for only 1% by mass, so it was not detected in the FT-IR spectrum. The strong fluorescence peak at 470nm in the subsequent fluorescence spectrum proved that TPE-NH 2 -HMSNs were successfully synthesized.

[0082] In the FT-IR spectrum of Au / CuNCs@HMSNs, at 1610 cm -1 The peak at 1000-1250cm -1 Si-O vibration in the region, from TPE-NH 2 -HMSNs. Therefore, the successful preparation of Au / CuNCs@HMSNs composites can be confirmed by FT-IR spectroscopy.

[0083] (2) Fluorescence performance characterization

[0084] like Figure 3 As shown in (b), under the excitation wavelength of 355 nm, Au / CuNCs@HMSNs has two characteristic emissions at 470 nm and 610 nm, respectively, which proves the successful synthesis of the composite material Au / CuNCs@HMSNs and indicates that the ratio fluorescence sensing system is successfully prepared.

[0085] (3) X-ray diffraction characterization (XRD)

[0086] Reference standards (JCPDS), such as Figure 4 As shown in (a), the XRD spectrum of Pen-Au / CuNCs showed diffraction peaks around 2θ at 43.1° and 44.3°, corresponding to the (111) plane of Cu and the (200) plane of Au, respectively, confirming the formation of high crystallinity Pen-Au / CuNCs.

[0087] (4) X-ray photoelectron spectroscopy (XPS)

[0088] At the same time, the element types and valence states of Au / CuNCs@HMSNs were confirmed by XPS measurements. Figure 4 As shown in (b), six main peaks appeared in the XPS spectrum, including Cu(2p), O(1s), N(1s), C(1s), S(2p), Si(2p) and Au(4f), indicating that Au / CuNCs@HMSNs are mainly composed of Cu, O, N, C, S, Si and Au. In addition, no characteristic peaks appeared, indicating the presence of Cu(0) and Cu(I) instead of Cu(II). At the same time, the valence state of the Au element in Au / CuNCs@HMSNs was also measured. Figure 4 As shown in (d), the peaks at 88.1eV and 84.4eV represent Au 4f 5 / 2 and Au 4f 7 / 2 The binding energy of Au / CuNCs@HMSNs is between that of Au(0) and Au(I). Therefore, all the above results prove the successful preparation of Au / CuNCs@HMSNs.

[0089] (5) Transmission electron microscopy (TEM) characterization

[0090] The morphology of the prepared Pen-Au / CuNCs was observed by TEM images. Figure 5 As shown in (a), dynamic light scattering (DLS) shows that Pen-Au / CuNCs are composed of small clusters with a diameter of 2.57±1.89nm. The Pen-Au / CuNCs aggregates show a dense flake structure with a diameter increasing to about 600nm, indicating that the fluorescence originates from the AIE of dense aggregates, which is consistent with the solid-state luminescence properties of Pen-Au / CuNCs powder. Therefore, the PL mechanism of Pen-Au / CuNCs may be due to the synergistic effect of the following two: (1) LMCT of Pen-Au / CuNCs from sulfur atoms of Pen to Cu(Au) atoms, and (2) restriction of intramolecular motion.

[0091] TPE-NH 2 -TEM images of HMSNs Figure 5 As shown in (b), TPE-NH 2 -HMSNs are well spherical, well dispersed, smooth on the surface, and have a similar particle size of about 600 nm. 2 A spherical cavity of approximately 480 nm is clearly visible in the HMSNs, and TPE-NH 2 -Some small mesopores in HMSNs. TPE-NH 2 The particle size distribution of -HMSNs was also evaluated by DLS to provide further support. Figure 5 (b) shows that the particle size of HMSNs is 588 ± 5.89 nm, indicating that the particles are evenly dispersed. 2 -Successful formation of HMSNs.

[0092] TEM images of Au / CuNCs@HMSNs are shown in Figure 2. Figure 5 As shown in (c), Au / CuNCs@HMSNs are well spherical with a particle size of about 700 nm. In addition, the spherical cavity of Au / CuNCs@HMSNs becomes smaller and the shell is 2 times thicker, which proves that TPE-NH 2 -HMSNs and Pen-Au / CuNCs were successfully electrostatically adsorbed. Figure 3-5 As shown in DLS of (c), the particle size of Au / CuNCs@HMSNs is 675.87±9.33nm, indicating that the particles are evenly dispersed. This indicates the successful formation of Au / CuNCs@HMSNs.

[0093] (6) Zeta potential

[0094] like Figure 5 (d) Due to the deprotonation of Pen carboxyl groups on the surface of Pen-Au / CuNCs, Pen-Au / CuNCs are negatively charged with a Zeta potential of -19.20 mV. 2 The protonation of the amino groups on the surface of -HMSNs resulted in a positive charge with a Zeta potential of +36.43 mV. 2 The Zeta potential of -HMSNs decreased to +29.36 mV, indicating that Pen-Au / CuNCs and TPE-NH 2 -HMSNs have electrostatic interactions. The above results indicate the successful formation of Au / CuNCs@HMSNs.

[0095] 3. Stability investigation of Au / CuNCs@HMSNs

[0096] In order to investigate the stability of the synthesized Au / CuNCs@HMSNs, the pH, temperature and storage time stability were investigated. The results are as follows Figure 6 (ac) shows that the fluorescence intensity of the material is low under alkaline conditions, but its fluorescence intensity is relatively stable under acidic conditions. This is because in a solvent environment with a pH value of 2.66, the deprotonation and protonation of the surface groups of the gold-copper clusters maximize the electrostatic interaction between the two particles. These effects greatly enhance the composition and arrangement of the molecules and reduce energy loss through non-radiative rotational relaxation channels, thereby significantly improving the emission efficiency. Therefore, the acidic environment can maintain the stability of the fluorescence intensity of Au / CuNCs@HMSNs. In a wide temperature range, the fluorescence intensity can be maintained at an ideal effect, and it can still have good fluorescence intensity after being stored in a refrigerator at 4°C for one month. This shows that the composite material has good stability, and also screens a suitable interval for the optimization of pH and temperature conditions in the subsequent detection system, where the pH stability interval is 2.0-3.0 and the temperature stability interval is 5-35°C.

[0097] 4. Construction and mechanism of hydrogen sulfide dual-emission detection platform

[0098] In the construction of dual-emission sensing system using Au / CuNCs@HMSNs and H 2 In order to explore the feasibility of this method, Pen-Au / CuNCs and TPE-NH 2 The fluorescence spectra of Au / CuNCs@HMSNs and Au / CuNCs@HMSNs respectively, and the fluorescence spectra of H 2 Fluorescence spectrum of S and Au / CuNCs@HMSNs mixed solution. The results are as above Figure 3-3(b) shows that the maximum emission wavelength of Pen-Au / CuNCs itself is at 610 nm, while that of TPE-NH 2 -HMSNs have a maximum emission wavelength of 470nm, and the composite Au / CuNCs@HMSNs has dual emission fluorescence peaks at 470nm and 610nm. 2 S, the peak intensity at 610nm decreased significantly, and the peak intensity at 470nm remained almost unchanged, indicating that H 2 S has a strong response to the constructed dual-emission system. In summary, a dual-emission fluorescence detection platform based on Au / CuNCs@HMSNs was established for H 2 Determination of S.

[0099] We further investigated the ratiometric probe for H 2 The sensing mechanism of S. Figure 7 As shown in (a), due to H 2 The absorption peak of S does not overlap with the excitation and emission of Pen-Au / CuNCs, firstly excluding the quenching effect caused by the inner filter effect (IFE) and fluorescence resonance energy transfer (FRET). Secondly, the ultraviolet-visible absorption spectrum (UV-vis) was measured, as shown in Figure 7 As shown in (b), Pen-Au / CuNCs has an obvious absorption band at 240 nm. 2 With the addition of S, the absorption peak red-shifts. Therefore, it is preliminarily speculated that Cu and H 2 The strong interaction between the two groups changed the original electron transfer mechanism of Pen-Au / CuNCs, resulting in the decrease and quenching of fluorescence. 2 The fluorescence lifetime of Au / CuNCs@HMSNs at 610 nm before and after S was investigated to study the quenching mechanism. The average lifetime τ was calculated according to the following formula (1):

[0100]

[0101] τ 1 and τ 2 is the short / long lifetime component of the fluorescence lifetime, and A 1 and A 2 Represents their respective relative coefficients. Figure 7 As shown in (c), in the absence of H 2 In the presence of S, the fluorescence lifetime of Au / CuNCs@HMSNs is 3.15 μs. 2 In the presence of S, its fluorescence lifetime is reduced to 2.18 μs, which again proves that the cause of fluorescence quenching is charge transfer. The decrease in the fluorescence lifetime of Au / CuNCs@HMSNs is attributed to the interaction between Pen-Au / CuNCs and H2 The metal-ligand coordination between Au / CuNCs@HMSNs and the charge transfer process will lead to faster exciton decay and shorter fluorescence lifetime. 2 XPS spectra when S exists. The results are as follows Figure 7 As shown in (d), two characteristic peaks are observed in the spectrum of Cu 2p at 932.6 eV and 952.5 eV, which can be attributed to the presence of Cu(0) and Cu(I). In addition, a satellite peak is observed at 942.6 eV, indicating that the addition of H 2 There is Cu(II) in Au / CuNCs@HMSNs after S. Therefore, the quenching mechanism is attributed to the interaction between copper and H in Pen-Au / CuNCs. 2 The high coordination effect between Cu and S leads to the formation of Cu-S bonds, which leads to non-radiative electron / hole recombination and annihilation in the efficient electron transfer process. 2 The yellowing of Au / CuNCs@HMSNs solution under natural light is caused by the Au part in Pen-Au / CuNCs. When the copper-gold ratio in Pen-Au / CuNCs is less than 1:1, the solution turns yellow, and the higher the Au ratio, the yellower the solution.

[0102] 5. Optimization of hydrogen sulfide detection conditions

[0103] In order to obtain H 2 The best experimental conditions for S detection were determined by I 610 / I 470 The changes in pH values ​​were studied to study the effects of pH, temperature and reaction time on the detection of the sensing system.

[0104] (1) pH optimization

[0105] The pH of the detection system solution directly affects the stability of the sensing system and is one of the important experimental conditions that affect the performance of the sensing system. In order to determine the optimal pH value for the fluorescence response of Au / CuNCs@HMSNs, the pH of the solution under different pH conditions where the material is stable was investigated. 2 The fluorescence response of S to Au / CuNCs@HMSNs. Figure 8 As shown in (a), when the pH value of the system is 3.0, I 610 / I 470 The reason may be that as pH increases, electrostatic interactions decrease, resulting in increased energy loss, which in turn leads to decreased fluorescence and decreased H 2 Insensitive response of S. In order to obtain high sensitivity, PB buffer with pH = 3.0 was used in subsequent experiments.

[0106] (2) Temperature optimization

[0107] Temperature is an important condition that affects the fluorescence sensing system. In order to control the optimal value of the fluorescence response of Au / CuNCs@HMSNs, the fluorescence response of Au / CuNCs@HMSNs in the temperature range of 15℃~45℃ was investigated. Figure 8 As shown in (b), when the temperature is 25℃, I 610 / I 470 The value is the largest, indicating that at 25 °C, Au / CuNCs@HMSNs and H 2 The S reaction had the best incubation effect and the best fluorescence response. This may be due to the thermal motion of the molecules and the thermal reaction effect of adsorption. When the temperature rises, the molecular thermal motion increases, and H 2 S is more likely to be adsorbed around the fluorescent response monomer to produce a fluorescent effect, but too high a temperature will also inhibit the adsorption. Therefore, the subsequent reaction temperature was set at 25°C.

[0108] (3) Time Optimization

[0109] Reaction time is also one of the key factors affecting the sensing effect. Figure 8 As shown in (c), with the increase of reaction time, I 610 / I 470 The value gradually increases and tends to be stable after 10 minutes, that is, the detection system reaches equilibrium, so the subsequent reaction time is selected as 10 minutes.

[0110] 6. Linearity and range

[0111] Au / CuNCs@HMSNs exhibited two fluorescence emission peaks at 470 nm and 610 nm under a single excitation wavelength of 355 nm. The fluorescence emission peak at 470 nm was the emission of Pen-Au / CuNCs, and the emission peak at 610 nm was the emission of TPE-NH 2 -Emission of HMSNs. Add H 2 After S, the fluorescence emission peak at 610nm (I 610 ) intensity decreased, and the fluorescence emission peak at 470nm (I 470 ) intensity remains almost unchanged. Under the above optimal detection conditions, using H 2 The different responses of S to the two fluorescence peaks of Au / CuNCs@HMSNs established a new method to detect H 2 S method. Fig. 9 As shown in (a), when H 2 When the S concentration increased from 0.5 μM to 40 μM, TPE-NH 2 The fluorescence emission peak intensity of -HMSNs at 470nm remained almost unchanged, while the fluorescence emission peak intensity of Pen-Au / CuNCs at 610nm gradually increased. The ratio of the two emission peak fluorescence intensities (I 610 / I 470 ), the ratio of the blank group is recorded as F 0 , H 2 The ratio of group S is recorded as F. Fig. 9 As shown in (b), H 2 The concentration of S was in the range of 0.5 to 40 μM and F 0 -F value shows a good linear relationship, and its linear fitting equation is F 0 -F=0.0165CH 2 S+0.1467(R 2 =0.9996), the detection limit (LOD) was 0.147 μM, and the quantification limit (LOQ) was 0.445 μM (LOD = 3.3σ / S, LOQ = 10σ / S). 2 As the concentration of S increases, the fluorescence color of the system changes from red to blue, which is consistent with the CIE Figure 1 To Fig. 9 (c)). In addition, it also changes from colorless to light yellow under natural light.

[0112] 7. Exclusive inspection

[0113] In order to investigate the established dual-emission detection system, the 2 S, whether it has good specificity, and explore the impact of interfering substances that may exist in actual samples on the detection system, as well as the impact of some sulfur-containing compounds. Therefore, the above-mentioned established method was used to investigate the impact of interfering substances in plasma samples and lake water samples on the analysis of the analytes.

[0114] First, we examine the detection of H 2 The selectivity of the S system was determined by adding 25 μM H 2 S and 10 times the concentration of glucose, glycine, arginine, histidine, cysteine, glutathione, homocysteine, sodium thiosulfate, sodium sulfate, potassium bromide, potassium chloride, sodium chloride, magnesium chloride, copper sulfate, and mercuric chloride were added to the constructed detection system, respectively. 0 -F is an indicator to compare the selectivity of the detection system. The results are as follows Fig.10 The results showed that the detection of interfering substances such as amino acids, ions and sulfur-containing compounds that may exist in actual samples did not have strong interference, indicating that the detection system was effective in determining H 2 S has good selectivity.

[0115] Re-examination of detection H 2 The anti-interference property of the S system was improved by adding 25 μM H 2S was added to the constructed detection system together with 10-fold concentration of glucose, glycine, arginine, histidine, cysteine, glutathione, homocysteine, sodium thiosulfate, sodium sulfate, potassium bromide, potassium chloride, sodium chloride, magnesium chloride, copper nitrate, and mercuric chloride. 0 -F is an indicator, comparing the above interfering substances with H 2 The effects of S coexistence are as follows. Figure 3-10 The results show that the detection system is effective for determining H 2 S has good anti-interference performance.

[0116] 8. Determination of hydrogen sulfide in actual samples

[0117] In order to determine whether Au / CuNCs@HMSNs have good practicality, the 2 The biological samples (plasma) and environmental samples (lake water) of S were tested. First, the samples were processed to confirm whether H 2 S, and then the spike recovery experiment was performed by adding 2.00, 15.00 and 30.00 μM H 2 The Au / CuNCs@HMSNs system was used to detect the samples. The results are shown in Table 1. The sample recoveries were 97.43% to 106.0%, and the RSDs were in the range of 1.3% to 3.0%, indicating that the determination method established in this study can be used for H in actual samples. 2 Detection of S.

[0118] Table 1 Effect of Au / CuNCs@HMSNs on H 2 Recovery results of S fluorescence response

[0119]

[0120] 9. Visual determination of hydrogen sulfide using solid sensors

[0121] In order to construct a convenient, economical and simple H 2 S determination device, a new solid sensing device was developed using the dual-emission sensing system and hydrogel beads. Fig.11 (a)), which can be detected semi-quantitatively by naked eyes or by taking photos with a mobile phone for quantitative analysis based on color changes.

[0122] First, in H 2 During the determination of S, as H 2 As the S concentration increases within the range of 0.5 to 200 μM, the hydrogel beads change color from colorless to light yellow under natural light and can be used for H 2 Preliminary qualitative detection of S. At the same time, with the H 2As the concentration of S increases, the sensor shows a series of color changes from red to blue under the irradiation of a portable UV lamp (such as Fig.11 (b)) realizes H 2 Visualization and quantitative determination of S. The color changes were collected by taking photos with a smartphone, and the RGB values ​​of the photos were analyzed and recorded using the Image J website tool. The changes in RGB values ​​are mainly represented by R (red), G (green), and B (blue). We extracted and analyzed the R, G, and B values ​​respectively. The study found that (G+B) / R and H 2 The S concentration showed a good linear relationship ( Fig.11 (b)), the linear range is 0.5~200μM, and the linear relationship is (G+B) / R=0.2049CH 2 S+1.4170(R 2 =0.9969), and the LOD was 0.265 μM.

[0123] In order to explore the specificity of the hydrogel beads and smartphone sensing platform, the possible interfering substances in serum and lake water were studied using this sensing platform. 2 The S concentration was 25 μM, and the interference concentration was 10 times the above concentration. Fig.12 As shown, compared with other possible interferents, H 2 S had the strongest response to hydrogel beads, while other interfering substances had little effect on the measurement results. The results showed that the fluorescent hydrogel beads and smartphone integrated platform had good specificity.

[0124] In order to determine whether the hydrogel beads and smartphone platform based on Au / CuNCs@HMSNs have good practicality, 2 First, the sample was processed to confirm whether H 2 S, and then the spike recovery experiment was performed by adding 15.00, 75.00 and 150.00 μM H 2 The results are shown in Table 2, with recoveries ranging from 85.63% to 97.98% and RSDs ranging from 3.7% to 7.2%, indicating that the established hydrogel beads and smartphone platform can be used for H 2 Detection of S.

[0125] Table 2 Effect of Au / CuNCs@HMSNs hydrogel beads on H 2 Recovery results of S fluorescence response

[0126]

[0127] 10. Comparison with other methods

[0128] This work uses ratiometric fluorescence sensing and smartphone readout to achieve H 2 Quantitative visualization of S. Single detection mode is easily affected by the test environment. In contrast, the dual-mode detection platform provides a cross-reference of the two modes to establish a built-in correction for environmental influences, effectively avoiding the shortcomings of a single detection mode and being more conducive to real-time on-site detection. In addition, as shown in Table 3, compared with other previously reported detection methods, 2 Compared with other methods for detecting S, the present method (last column) has a wider linear range (0.5-40 μM) and a lower detection limit (0.15 μM).

[0129] Table 3 Different fluorescence analysis methods were used to determine H 2 Performance comparison of S

[0130]

[0131] summary

[0132] In this study, we successfully constructed a novel ratiometric fluorescence sensing system (Au / CuNCs@HMSNs) using Au / CuNCs with excellent fluorescence properties and easily synthesized hollow mesoporous silica containing AIEgens for the selective detection of H 2 S, and established two analytical methods: solution sensing and solid portable sensing. 2 Modification on hollow mesoporous silica greatly improves its water solubility, is safe and non-toxic, and expands the contact area with the analyte, improving the detection effect. At the same time, as a reference fluorescence in the ratio fluorescence sensing system, the blue fluorescence emission remains unchanged. Gold-copper nanoclusters act as recognition fluorescence, and due to the charge transfer from ligand to metal, they exhibit AIE effect, producing strong red fluorescence. When the complex is exposed to H 2 When in S, the copper and H 2 The high coordination effect between S produces Cu-S bonds, leading to non-radiative electron / hole recombination and annihilation in the effective electron transfer process, thereby quenching the red fluorescence emission and achieving the transition of the fluorescence color from red to blue. The formula for fluorescence intensity in solution is F 0 -F in the range of 0.5~40μM increases with the increase of H 2 The increase in S concentration is consistent with other previously reported H 2 Compared with the method of S, the detection limit is lower (0.147 μM). Based on this, hydrogel beads were developed, and the RGB values ​​of the corresponding hydrogel beads were read using the color recognition software on the smartphone. 2 The relationship between S realizes H 2The quantitative visualization detection of S maintains good linearity in a wide range (0.5-200 μM) with a detection limit of 0.265 μM. The dual modes of ratiometric fluorescence sensing and smartphone platform sensing can avoid the shortcomings of a single detection mode and have the characteristics of high selectivity, high sensitivity, simplicity, economy, safety and non-toxicity, which can provide a reference for the detection of H in actual water samples and biological samples. 2 S monitoring provides a convenient, reliable, simple and easy detection method.

Claims

1. A ratiometric fluorescence sensing system based on aggregation-induced emission, characterized in that: Prepared as follows: (1) Preparation of TPE-NH2-HMSNs Amine-modified tetraphenylethylene TPE-NH2 and hexadecyltrimethylammonium bromide CTAB were mixed and dissolved in an ethanol solution, ammonia water was added and stirred, and tetraethoxysilane TEOS was dropped into the solution to react to obtain initial mesoporous silica TPE-NH2-MSNs with a mesoporous template CTAB; the initial TPE-NH2-MSNs were added to water and heated at about 90°C to react to obtain TPE-NH2-HMSNs; (2) Preparation of Pen-Au / CuNCs Dissolve penicillamine Pen in water under stirring at room temperature in the dark, add HAuCl4 tetrachloroauric acid, then add copper nitrate Cu(NO3)2, stir to obtain a white suspension, stir under room temperature in the dark, wash by centrifugation, and then dry to obtain dry Pen-Au / CuNCs powder; (3) Preparation of Au / CuNCs@HMSNs Pen-Au / CuNCs and TPE-NH2-HMSNs were mixed, and then water was added, shaken vigorously, and finally ultrasonicated, centrifuged, and dried to obtain Au / CuNCs@HMSNs powder.

2. The ratiometric fluorescence sensing system based on aggregation-induced emission according to claim 1, characterized in that: Prepared as follows: (1) Preparation of TPE-NH2-HMSNs Dissolve 0.001-0.06 g TPE-NH2 and 0.2-1.2 g CTAB in 100-500 mL ultrapure water and 80-280 mL ethanol; ultrasonically treat the mixture for 20-30 min until CTAB is completely dissolved; then, add 2-18 mL ammonia water to the mixture and stir for 1-2 h; finally, add 2-18 mL TEOS is added dropwise to the solution and reacted at 30-40°C for 6-7h; the obtained mixture is filtered, separated, washed, and dried to obtain initial mesoporous silica TPE-NH2-MSNs with a mesoporous template CTAB; next, 0.1-2.5g of the initial TPE-NH2-MSNs is added to 100-500mL of distilled water and heated at 90-100°C for 12-36h to synthesize a hollow structure, remove the mesoporous template CTAB, and expand the pore size; after the reaction is completed, the crude product TPE-NH2-HMSNs is obtained by centrifugation at 10000rpm for 10-15min, and the crude product is purified by washing with ethanol and water three times; the purified TPE-NH2-HMSNs is freeze-dried for more than 12h to obtain a dry TPE-NH2-HMSNs powder; (2) Preparation of Pen-Au / CuNCs Under magnetic stirring at room temperature in the dark, 60-260 mg of Pen was completely dissolved in 10-100 mL of ultrapure water; then, 2-50 mM HAuCl4 was added first, and then 0.01-0.9 M Cu(NO3)2 was added, and after stirring for 5-10 min, a white suspension was obtained, indicating the formation of Pen-Au / CuNCs; the solution was stirred at room temperature in the dark for 2-4 h; then, in order to remove excess ligands, the obtained Pen-Au / CuNCs solution was centrifuged and washed, and the collected precipitate was dried to obtain dry Pen-Au / CuNCs powder; (3) Preparation of Au / CuNCs@HMSNs 0.01-0.1 g Pen-Au / CuNCs and 0.005-0.035 g TPE-NH2-HMSNs were mixed, and then 10-100 mL ultrapure water was added, and the mixture was shaken vigorously for 2-5 min, and finally ultrasonically treated for 20-30 min to obtain an Au / CuNCs@HMSNs solution and stored at 4°C; the Au / CuNCs@HMSNs solution was centrifuged and washed, and the collected precipitate was dried to obtain Au / CuNCs@HMSNs powder.

3. The aggregation-induced luminescence ratiometric fluorescence sensing system according to claim 1 or 2 is applied to the rapid detection of H2S in biological samples and environmental samples.